Lalon Shah, the great poet - Hossain, Abu Ishahaq, 1974- (Palal Prokashoni, 2009)
Study on life and works of Lālana Śāha, 1774-1890, Bengali nomadic folk poet from Kushtia in undivided Bengal, India, now part of Bangladesh; includes translations of songs of the poet.